2002
DOI: 10.1590/s0066-782x2002000500006
|View full text |Cite
|
Sign up to set email alerts
|

Repair of an Atherosclerotic Coronary Artery Aneurysm by Implantation of a Coronary Covered Stent

Abstract: An atherosclerotic aneurysm of the right coronary artery complicated by a recent myocardial infarction was successfully treated with coronary artery stenting, using a device consisting of 2 stents with a layer of expandable polytetrafluorethylene (PTFE) placed between them. A follow-up angiograph 5 months after the procedure showed sustained initial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Approximately, 40% were managed conservatively, 27% has coil embolization, 27% had surgical treatment, and 13% had catheter-mediated occlusion of the fistula. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Dodge-Khatami et al 17 have classified CAFs as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 40% were managed conservatively, 27% has coil embolization, 27% had surgical treatment, and 13% had catheter-mediated occlusion of the fistula. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Dodge-Khatami et al 17 have classified CAFs as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transcatheter closure is the safe and preferred method for anatomic approachable vessels. [2][3][4]8,[14][15][16]…”
Section: Discussionmentioning
confidence: 99%
“…Szalat et al (10) reported that PTFE-covered stents are effective and safe for large (diameter of 6 mm to 10 mm) atherosclerotic aneurysms (10). Portela et al (11) reported a follow-up angiograph five months after using a covered stent showing sustained initial results. The management strategies for coronary aneurysms are not clear, and each case should be managed on an individual basis depending on the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal thrombus formation and distal embolization result in myocardial ischemia or infarction [1]. It is known that Jostent \ coronary stent graft could be used for CAA therapy; however, there is limited experience about the treatment of thrombus containing CAA by stent graft implantation in the medical literature [1][2][3]. Therefore, here we report a patient who has atherosclerotic CAA containing thrombus treated successfully with Jostent \ coronary graft stent.…”
Section: Introductionmentioning
confidence: 96%